10‐3: Invited Paper: AM MLED backlight units on glass for 75‐inch LCD displays. Issue 1 (25th September 2020) - Xu, Hongyuan; Xiao, Juncheng; Fei, Jiayang; Zhao, Rui; Wang, Xu; Hao, Sikun; Qiu, Yongyuan; Liu, Jinfeng; Li, Yan; Zhuang, Jiaqing; Hu, Daobing; Zhang, Shengdong; et al.
Abstract : We developed AM miniLED local dimming (LD) backlight systems on glass for 75‐inch LCD displays, with each consisting of 5184 localing dimming zones. The 75‐inch display achieves a high dynamic contrast ratio of 1, 000, 000 : 1 and high brightness of more than 1000nits. This backlight system grants the LCD display with HDR performance, which is comparable to those of other products (Dual‐cells and OLEDs), by making the dark state real black. In addition, the system exhibits advantages such as low fabrication cost and long life time.